Pedagogical Support Mechanisms for Learners with Learning Barriers in South Africa: An Analysis Study - Michael Mbongiseni Buthelezi; Lethabo Clement Mametja (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Learners who experience barriers to learning continue to face challenges in accessing and fully participating in education, despite inclusive education policies in South Africa. This study aimed to explore how teachers at a primary school support learners with barriers to learning, with particular focus on accommodating learner diversity and promoting equitable access to education. The study was underpinned by an interpretivist paradigm and employed a qualitative research approach with a case study design. Data were collected through semi-structured interviews and document analysis. The sample comprised ten participants, including four teachers, four members of the school-Based Support Team (SBST), and two District-Based Support Team (DBST) officials from the Mopani West District, Makhutswe Circuit, Limpopo Province, South Africa. Data were analysed using thematic analysis. The findings revealed that teachers employed adaptive teaching strategies, curriculum differentiation, and collaborative support structures to address learner diversity. However, persistent challenges such as overcrowded classrooms, limited resources, and insufficient assistive technologies constrained effective implementation. The study concludes that while teachers, SBSTs, and DBSTs play a critical role in advancing inclusive education, systemic and resource-related barriers hinder optimal practice. It is recommended that stakeholder collaboration be strengthened, targeted professional development be enhanced, and inclusive education policies be more effectively implemented to support learners with barriers to learning.